Data not available? Survey applications to carbon sequestration and irrigation water quality - Gardner, Grant (Kansas State University, 2022)
Essay 1: Cover crop and no-till adoption: What affects willingness to accept of cover crop and no-till contracts? Carbon markets offer supplemental income to producers for implementing no-till and cover crop practices that sequester carbon in the soil. Using choice experiments, we find that 37% and 43% of our sample would not accept a hypothetical contract to enroll cover crop and no-till respectively, indicating that producers are unwilling to enroll in carbon contract offerings current payment rates. We estimate the marginal willingness to accept (MWTA) of producers for current contract attributes including contract length and portion of cropland enrolled for both cover crop and no-till. Using random parameters logit models, we find that MWTA of a cover crop contract for enrolling 33% of cropland acreage for a 5- and 10-year contract is $54.44/acre and $75.85/acre, or two to three times current program payments. We find comparable results with lower prices for no-till contracts. In addition to indications that current payments are too low to incentivize widespread adoption, we find that MWTA of contracts increases with contract length because contractual agreements constrain producer decision making. We also find indications that arid regions may not receive enough precipitation for cover crop implementation which causes higher MWTA of cover crop contracts. Results indicate that conservation practices and payments under existing carbon contracts will limit enrollment in Kansas and other semi-arid regions of the High Plains. Essay 2: Producer response to groundwater quality concerns: Are concerned producers watering less? Increases in irrigation intensity across the High Plains Aquifer have led to declining water levels and deterioration of water quality due to runoff and salts accumulation. In this paper, we combine a survey of producer groundwater perceptions with data on groundwater use to determine how ground water quantity and quality concerns affect irrigation water use. We find that as well yield (i.e., water quantity) concern increases, producers typically irrigate a smaller number of acres at each well which results in less total water use. However, we find that major concern over water quality corresponds with an increase of water use which is driven by producers watering more acres on the extensive margin. Our results indicate that water quality concerns mitigate the declines in irrigation water use caused by well yield concerns. When major water quality concern is present, producers apply 11.45 more acre-feet of water per well. We do not find significant changes in water use on the intensive margin due to well yield or water quality concerns. In looking at the effects of water quality concern on crop choice, we find that the planting decisions of producers with water quality concerns are not statistically different from producers without concern, which indicates producers are not changing their crop choice on average due to concern over water quality.
Keywords: Cover crop; Carbon sequestration; No-till; Irrigation water quality; High Plains Aquifer; Water use